MEANINGFUL WORK AS AN ANTECEDENT OF RETIREMENT. (11th November 2018) - Fisher, G; Steger, M F; Sonnega, A; Ryan, L H
Abstract: Meaningfulness of work has been cited as one of many psychological reasons for and benefits of working. Although prior research has theorized that meaningfulness of work is an antecedent of retirement, little empirical research has been conducted to investigate meaningfulness of work in relation to retirement plans and behavior. Using panel data from the HRS collected between 2012–2016, the present study investigates perceptions of meaningfulness of work among N=944 individuals who completed a unidimensional 10-item meaningfulness of work module in the 2014 wave of the HRS (M=4.37, SD=.71). We will summarize descriptive statistics about meaningfulness of work, and how meaningfulness relates to retirement expectations, retirement behavior, and retirement adjustment as well as other antecedents and outcomes of the retirement process. We will discuss the findings in relation to extant retirement research and describe implications for workers, their employers, and society in general.